Jurisprudence Education for Women Through Community Women's Studies Ngembel Hamlet, Baosan Lor Ngrayun Village, Ponorogo - Ratna Utami Nur Ajizah; Shofi Imroatus Sholikhah; Febriana Wahyuning Tyas; Haifa Ayu Thursina; Suciana Winuryani; Muhammad Hisyam Al Fath (Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Social, educational, and limited religious knowledge gaps in the community result in a lack of understanding of how fiqh should be an important basis for everyday life, even when you have a family. The cultivation of fiqh should have been known from an early age by Muslims, but what happened to the women and young women of the women's mosque in the Ngembel hamlet, Baosan Lor village, was the exact opposite, where knowledge about women's fiqh was very minimal. For example, when they are in a junub state, after giving birth, even when they are drunk, they don't know what they should do after that. This research uses the Participatory Action Research (PAR) research method where the research method is carried out in a participatory manner among members of the community in a community whose enthusiasm is to encourage changes in perspectives and attitudes in society from ignorance to knowing and understanding (changes in living conditions for the better). and right). The researchers as well as the initiators in the women's fiqh study program were moved because of the problems that existed in the community with the aim of imparting knowledge to women's women's mosques and young women in the community there. Enthusiasm was also seen after the women and young women of the mosque gained knowledge about fiqh and became enlightened and many also asked questions about problems in everyday life.